Does a family history of prostate cancer affect screening behavior in Jamaican men? - Belinda F. Morrison; Yulit Gordon (Pan American Health Organization, 2018)
Objective. To determine 1) the characteristics of males with a family history of prostate cancer who presented for screening and 2) the association between family history and diagnosis of prostate cancer in a cohort of screened Jamaican men. Methods. The study consisted of a prospective cohort of black men who screened at the Jamaica Cancer Society in Kingston between 2006 and 2016. Data were collected on: 1) age at screening and age at diagnosis of prostate cancer, 2) family history of prostate cancer, and 3) prostate-specific antigen (PSA) and digital rectal examination (DRE) findings. Results. Approximately 600 (21.4%) of screened men who reported data on family history (2 791 / 2 867) said they had a family history of prostate cancer. Men with a family history of prostate cancer 1) commenced screening at a younger age than men without a family history (P <0.001) and 2) tended to have a younger age at diagnosis of prostate cancer (P = 0.262). There was no significantly increased risk of prostate cancer in men with a reported family history of prostate cancer (odds ratio: 1.4; 95% confidence interval: 0.821-2.386; P = 0.217). Conclusions. Men with a family history of prostate cancer presented frequently for screening and earlier than those without. There was a lack of association between family history of prostate cancer and diagnosis. Further studies are needed to investigate this association and validate family histories.